The Effectiveness of Law Enforcement Against Smuggling of Imported Used Clothes: An Analysis Based on Positive Law in Indonesia - Ridwan, Salwa Billa Mirza; Azhari, Aidul Fitriciada (Universitas Muhammadiyah Yogyakarta, 2024)
This study examines the legal challenges surrounding the smuggling of imported used clothing in Indonesia, addressing factors such as geographical complexities, resource limitations, organized crime networks, and corruption within law enforcement agencies. The manuscript aims to answer key research questions through an exploration of international legal frameworks, including the United Nations Convention against Transnational Organized Crime and World Trade Organization agreements. The findings emphasized the necessity for enhanced infrastructure, technology, inter-agency cooperation, and anti-corruption measures to improve enforcement effectiveness. Education and international collaboration are proposed as vital strategies to combat cross-border smuggling networks. Ultimately, this research contributes novel insights into legal strategies needed to address the complex challenges of smuggling imported used clothing, ensuring comprehensive and sustainable solutions to safeguard national interests and public safety.